Three Chapters on Courtly Love in Arthurian France and Germany Lancelot-Andreas Capellanus-Wolfram von Eschenbach's "Parzival" - Weigand, Hermann J. (UNC Studies in the Germanic Languages and Literatures, 1956)
By analyzing Chrétien's "Cligès", Ulrich von Zatzikhoven's "Lanzelet", Chrétien's "Chevalier de la Charette", and the Old French "Prose Lancelot", as well as Andreas Capellanus' "De Amore" and Eschenbach's "Parzival", Weigand presents a picture of the ideals of courtly love in Europe in the latter half of the twelfth and beginning of the thirteenth centuries. A long chapter on "Parzival" focuses especially on the introduction of Christian themes and changing ideas of the compatibility of love and marriage.